PENAMAAN PULAU-PULAU KECIL DI KABUPATEN PULAU MOROTAI BERDASARKAN KAJIAN TOPONIMI DAN PERSEPSI ETNOLINGUISTIK - Rahmat Muhidin (Balai Bahasa Provinsi Papua, 2018)
AbstractThe research discussed about names of island in Morotai Island Regency in its relationship with the history of entitling of the island by people around Morotai Island Regency. This research aims to describe names of the island in Morotai islands Regency North Maluku Province with toponimy and ethnolinguistics study. The method used in this research was descriptive method and literature study. The data in this research were secondary data, survey data of island toponimy and analyzing data as an approach of entitling of the island in Morotai Island Regency. The result showed that entitling of the island in Morotai Island Regency referred to some indicators: (1) Entitling the islands based on Morotai Islands Regency: Pulau Babi/Tabisasu, Bobongone Maharum, Burung, Dodola Besar, Dodola Kecil, Galo-Galo Besar, Galo-galo Kecil, Jujurum, Kacuwawa, Kapa-kapa, Kokaya, Kolorai, Loleba Kecil (Loleba means rope that is used to tie housetop), Lum-lum (name of a kind of mushroom), Mitita Karang, Morotai (Moro means supernatural creature/sacred person/wind) (Tai means there), (Morotai means there is a supernatural creature/sacred person/wind there), Ngele-Ngele Besar (Ngele-ngele means rope that is used to hang fishes up), Ngele-Ngele Kecil, Pelo Patok, Rao, Rube-rube (rube-rube means water/jar for water), Ruki-ruki (name of a tree), Saminyamau, Sarang Burung Besar, Sarang Burung Kecil, Tabailenge, Tanjung Garam Besar, Tanjung Garam Kecil, and Zum-zum, (2) Name sare correlated with vegetation of trees, animal, and based on the origin of certain creature. AbstrakPenelitian ini membahas nama-nama pulau di Kabupaten Kepulauan Morotai Provinsi Maluku Utara yang berhubungan dengan sejarah penamaan pulau oleh warga sekitar pulau di Kabupaten Pulau Morotai. Penelitian bertujuan untuk mendeskripsikan nama-nama pulau di Kabupaten Pulau Morotai berdasarkan kajian toponimi dan etnolinguistik. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dan studi literatur, data sekunder, data survei toponimi pulau, dan pengolahan data sebagai ancangan penelitian penamaan pulau-pulau di Kabupaten Pulau Morotai.Hasil penelitian menunjukkan bahwa penamaan pulau di Kabupaten Pulau Morotai mengacu pada beberapa indikator: (1) Nama Pulau yang terdiri dari Pulau Babi/Tabisasu, Bobongone Maharum, Burung, Dodola Besar, Dodola Kecil, Galo-Galo Besar, Galo-Galo Kecil, Jujurum, Kacuwawa, Kapa-Kapa, Kokaya, Kolorai, Loleba Kecil: tali pengikat atap rumah, Lum-lum nama jamur, Mitita/karang, Morotai Moro artinya mahluk gaib/orang sakti /angin, tai artinya di sana